Postacute Management of Older Adults Suffering an Osteoporotic Hip Fracture: A Consensus Statement From the International Geriatric Fracture Society. (15th July 2020) - Reyes, Bernardo J.; Mendelson, Daniel A.; Mujahid, Nadia; Mears, Simon C.; Gleason, Lauren; Mangione, Kathleen K.; Nana, Arvind; Mijares, Maria; Ouslander, Joseph G.
Background: The majority of patients require postacute care (PAC) after a hip fracture. Despite its importance, there is no established consensus regarding the standards of care provided to hip fracture patients in PAC facilities. Methodology: A writing group was created by professionals from the International Geriatric Fracture Society (IGFS) with representation from other organizations. The focus of the statements included in this article is toward PAC providers located in nursing facilities. Contributions were integrated in a single document that underwent several reviews by each author and then underwent a final review by the lead and senior authors. After this process was completed, the document was appraised by reviewers from IGFS. Results/Conclusion: A total of 15 statements were crafted. These statements summarize the best available evidence and is intended to help PAC facilities managing older adults with hip fractures more efficiently, aiming toward overall better outcomes in the areas of function, quality of life, and with less complications that could interfere with their optimal recovery.